Effect of Chitosan Dosage In Polyethersulfone (PES) Membrane Performance In Treating Palm Oil Mill Secondary Effluent (POMSE) Wastewater - Binti Adham, Nur Elmira Shafiqah; Ts Dr Nor Faizah Binti Razali, (Progress in Engineering Application and Technology, 2022)
Micro and ultra-filtration membranes are effective in removing a wide variety of dissolved pollutants. In this study, Palm Oil Mill Secondary Effluent (POMSE) been used to be treat. Palm Oil Mill Secondary Effluent (POMSE) is the wastewater that generated from Palm Oil Mill Effluent (POME). POMSE that treated using conventional method require about 30 to 60 days to fully be treated. Thus, Polyethersulfone-Chitosan (PES/CS) been synthesized in this study to reduce the time to treat POMSE wastewater. Therefore, the purpose of this study is to investigate the performance of Polyethersulfone (PES) membrane with the presence of chitosan with different dosage in treating Palm Oil Mill Secondary Effluent (POMSE) wastewater. The PES membrane will be synthesized with the chitosan with different dosage which are 0%, 0.25%, 0.75% and 1% produce Polyethersulfone-Chitosan (PES/CS) membrane to improve the performance of PES membrane. The characterization of the membrane been observed through Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR). The porosity of the membrane been observed by using SEM while the chemical composition of the membrane been observed using FTIR. The membrane performance of each different dosage of chitosan then been tested by using filtration method to treat the POMSE wastewater. According to the POMSE wastewater treatment results obtain in this study it is shown that PES/CS membrane with 0.75% of chitosan dosage is the most efficient to treat POMSE wastewater. In this research, it also shown that membrane technology only takes one day to treat POMSE wastewater while conventional method takes about 30 to 60 days to treat POMSE wastewater.